Influence of corn, soybean meal, wheat bran extracts on the bile tolerance of four strains of Lactobacilli - ZENG Dong; NI Xue-qin; HU Xiao-ling; ZHANG Hong; LIU Kun (浙江大学学报. 农业与生命科学版)
The effects of corn, soybean meal and wheat bran extracts on the viability of Lactobacilli were evaluated under simulated high bile level in the pig intestine. The viable counts of the tested strains JJB3, SNZ10, MNZ8 and KNZ4 were detected at the presence of the feed extracts added with 1.0% bile salt dissolved in pH 7.0 phosphate-saline buffer for 4 h. In order to evaluate the effect of the feed constituents on the cell survival, the individual effect of glucose and free amino nitrogen (FAN) was examined. The results indicate that the viable numbers showed a significant decrease (P<0.01) in the absence of feed extracts. L. reuteri MNZ8 decreased by 1.74 logarithm value, while L. reuteri KNZ4 dropped by 1.16 logarithm value. However, the viability of the four strains tested was improved significantly in the presence of feed extracts (P<0.05). The bile tolerance of the strain JJB3 was the strongest, while that of MNZ8 was relatively low among the strains tested. The viability rate of JJB3 was increased from 78.12% to 99.35%, 99.48%, 99.74% in the presence of corn, soybean meal and wheat bran extracts, respectively. The extent of improvement was related to the concentration of glucose and FAN, while glucose influenced the viability greatly. As a result, the best protecting effect was provided by wheat bran extracts, subsequently by soybean meal and corn.